Gender differences in patient-perceived changes to the system of values after a cancer diagnosis. Issue 4 (April 2022) - Greszta, Elżbieta; Świderska, Joanna; Zalewska-Łunkiewicz, Karolina; Obidziński, Michał; Ryś, Maria; Hamer, Katarzyna
Highlights: The diagnosis of cancer can influence the personal goals and value systems of patients. There are significant gender differences in the changes in the importance of values after a cancer diagnosis. In the treatment and counselling of cancer patients, gender differences and the value system should be considered. Abstract: Objective: The objective of the presented study was to investigate gender differences in the changes of value systems after a cancer diagnosis. Methods: In the study, we used the Polish adaptation of the Rokeach Value Survey and compared within-subject differences in the obtained results from before (retrospective) and after patients' cancer diagnosis . In the analysis, we used the Aranowska ω Coefficient of Choice and Single-Sample t -test statistics. Results: Generally, after cancer diagnosis communal values gained, and agentic - lost importance regardless of patients' gender. However, we found statistically significant effects of gender in value system changes, namely agency values ("independent" and "intellectual") become less important for men than women, while the communal value "Mature love" was placed higher by men than women. Conclusion: The results of the study confirm our initial hypothesis about significant gender differences in the changes of the value system. Practice implications: Obtained knowledge can be used to better predict patient motivation and behavior in the face of oncological treatment. It is important that gender differences are considered in the process of cancer patients treatment. It can be beneficial for communication between a doctor and a patient and for counseling regarding coping with the disease.